The effectiveness of visual learning methods: the definition of boundaries - N. A. Pervushina (Moscow Polytechnic University, 2022)
At the article it's posited the problem determining the boundaries of psychological approaches to the perception of visual information in the training. The possibility of combining different approaches in a single educational space is discussed on the methodological basis of information and synergetic conception of I.V. Melik-Gaykazyan. The article presents the results of the research project RFBR № 10-06-00313.